Advanced Assessment of Medical Students Clinical Performance: Challenges Methods and Approaches - Kayghobad Tahernezhad; Fatemeh Javidan (Kerman University of Medical Sciences, 2008)
Background: Assessment of clinical competencies is one of the complicated and hard tasks in medical education Nowadays assessment of clinical performance is significantly patient centered and student centered Traditional methods consisted of faculties observations oral examinations and multiplechoice tests Increased faculties workload discontent with traditional methods of clinical skill assessment and developments in the fields of psychology and education have led to the formation of new modalities in performance assessment methods with special definition Clinical competency is defined as the ability to gather information from the patient by history taking and physical examination integrating this information in order to make a diagnosis selecting appropriate laboratory tests to confirm the diagnosis and efficient disease management   At the present time several fields for future direction of performance assessment in medical education are suggested including:   a) Evidencebased locally developed assessments   b) Understanding educational outcomes and noncognitive assessment factors   c) Increase in studentdriven aspect of assessments   Attempting to introduce new and advanced medical students clinical performance assessment methods according to the world accredited centers this article analyzed three mentioned directions in field of clinical performance assessment Conclusion : Improvement of performance assessment in local or national level is a complex issue which needs time cooperation recourses and fundamental attempts However this is the price to pay if we believe that clinical competency can improve quality of patient care